Evaluasi Usability dan Perbaikan Desain Antarmuka Pengguna Website Perpustakaan Kota Malang menggunakan Metode Evaluasi Heuristik - Rahmad Zapriant Agiel Dzazuly; Widhy Hayuhardhika Nugraha Putra; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Malang city library has an official website to help the community in using services from a distance. The features offered range from viewing book collections to extending borrowing time online. Based on the results of interviews with one of the library members and observations, there were complaints or usability problems on the Malang city library website, there was no error message when the user entered an incorrect password or username and inconsistent language usage. Based on these problems, the evaluation and improvement of usability on the design of the Malang city library website interface uses the heuristic method to find usability problems based on 10 heuristic principles by evaluators. From the evaluation results, it was found that there were 45 problems found in 8 of the 10 heuristic principles. The heuristic principle with the highest percentage of finding problems is the heuristic principle (H-8) Aesthetic and minimalist design with 31.67% of all problem findings. While the heuristic principle that has the highest severity rating is the heuristic principle (H-5). Error prevention with a severity rating of 3.06 of the 4 problems found. From the findings of the problem, recommendations for improvement were given which were then reevaluated by the evaluator. The results obtained from the evaluation of the recommendations for improvement were 95.45% of the problems that were resolved from a total of 44 problems.